Making haste slowly : strengthening local environmental management in agricultural development - Savenije, H.; Huijsman, A. (Amsterdam, The Netherlands : Royal Tropical Institute, 1991)
Making haste slowly deals with environmental management of small scale agriculture in marginal areas. the focus is specifically on the local level as vital to the success of any national or international policies.
This study is volume 2 in the series Development Oriented Research in Agriculture.
Includes bibliographical references.
nmn, 10/08/2016
Loans
Keywords: Sustainable agriculture; Agriculture; Agricultural resources; Agriculture and state